2000
DOI: 10.1002/vnl.10244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impact modifiers on the properties of rigid PVC/wood‐fiber composites

Abstract: This study examined the effects of impact modifier types and addition levels on the mechanical properties of rigid PVC/wood‐fiber composites. The impact resistance of rigid PVC/wood‐fiber composites depends strongly on the type and content of impact modifier. With the proper choice of modifier type and concentration, the impact strength of rigid PVC/wood‐fiber composites can be significantly improved without degrading the tensile properties. Methacrylate‐butadiene‐styrene and all‐acrylic modifiers performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 15 publications
6
80
0
1
Order By: Relevance
“…Polypropylene has a solubility parameter of 9.4 (cal/cm 3 [14]. It can be observed that the solvent whose solubility parameter is closest to that of polypropylene (9.3) is benzene (9.1), followed by toluene (8.9) and finally xylene (8.8).…”
Section: International Journal Of Engineering and Technologies Vol 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Polypropylene has a solubility parameter of 9.4 (cal/cm 3 [14]. It can be observed that the solvent whose solubility parameter is closest to that of polypropylene (9.3) is benzene (9.1), followed by toluene (8.9) and finally xylene (8.8).…”
Section: International Journal Of Engineering and Technologies Vol 11mentioning
confidence: 99%
“…Other than that, the main drawback of the use of natural fibre as fillers is the low processing temperature permissible due to the possibility of fibre degradation and/or the possibility of volatile emissions that could affect the composite properties. Agro-residue or field crop such as cereal straw, flax straw, rice husk, bagasse, cornstalk, wheat straw and corncob which categorized as natural fibres are recently being considered as an alternative for the wood-plastic composites which are at present dominating the natural fibrecomposite market [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…High-density polyethylene-wood-flour composites were manufactured following the methods described in a previous paper [10]. HDPE, oven-dried wood flour, and coupling agents were dry-blended in a 20L high intensity mixer (Papenmeier, Type TGAHK20) for 5 min.…”
Section: Manufacture Of Hdpe-wood-flour Compositesmentioning
confidence: 99%
“…About 2.5 billion kg of fillers are currently used in plastic industry (Caulfield et al, 2005, La Mantia et al, 2005and Clemons, 2002. This provides rigidity and resistance to temperature (Abu-Sharkh et al, 2004 andMengeloglu et al, 2000) but costly and abrasive to the processing equipment (Mengeloglu and Matuana, 2003). The interest in using plastic as binder in composite board is attributed to its properties displayed and recently, organic fillers produced from wood or agricultural plants have gained tremendous attention from plastic industry.…”
Section: Introductionmentioning
confidence: 99%